Hydroxysafflor Yellow A Suppresses Platelet Activating Factor-Induced Activation of Human Small Airway Epithelial Cells - Guo, Xinjing; Zheng, Meng; Pan, Ruiyan; Zang, Baoxia; Jin, Ming (Frontiers in Pharmacology, 2018)
Hydroxysafflor yellow A (HSYA) is a chemical component isolated from the Chinese medicine Carthamus tinctorius L. HSYA has numerous pharmacological effects, including protecting against and mitigating some respiratory diseases such as acute lung injury and chronic obstructive pulmonary disease; however, its effect on asthma remains unclear. We previously found that HSYA attenuated ovalbumin-induced allergic asthma in guinea pigs. Platelet activating factor (PAF) is a phospholipid mediator of inflammation and an important factor in the pathological process of asthma. In this study, we investigated the anti-inflammatory effects of HSYA and its underlying mechanisms in PAF-induced human small airway epithelial cells (HSAECs). PAF-activated cells were pretreated with HSYA and/or the PAF receptor inhibitor, ginkgolide B, and we observed changes in the expression of interleukin (IL)-1β, IL-6, and tumor necrosis factor alpha, monolayer permeability of HSAECs, and inflammatory signaling pathways. HSYA attenuated the PAF-induced increase in expression of inflammatory factors and destruction of cell-barrier function, and inhibited the expression of protein kinase C, mitogen-activated protein kinases, activator protein-1, and nuclear factor-κB activation induced by PAF. These findings suggest that HSYA may represent a potential new drug for the treatment of asthma.